Modeling Store Characteristics as Antecedents of Impulse Purchase - Chaturvedi, Ramesh Kumar (Indian Journal of Marketing, 2013)
This research intended to give a specific answer to what in-store factors favorably influence impulse buying that retailers could use to their advantage. Indeed, it has a hedonic approach, yet, it is quite valuable from the retailer’s point of view. Many retailers face a problem - that in spite of strong footfalls, billing remains bleak, yet others have high billing proportion to footfalls. This research is an effort to solve this problem . It was hypothesized that numerous variables, controllable by retailers, are available inside a store and have the potential to influence impulse purchasing. An intercept survey at retail agglomerations in India was conducted, and detailed literature exploration was done to identify the in-store variables. These variables were reduced to ten in-store factors through factor analysis based on the shoppers’ response towards them. Regression modeling was done to predict impulse purchase based on in-store factors. The in-store factors were found to influence impulse purchase significantly. The relative weight of these factors was also found so that the retailers could prioritize their resources. Out of these ten factors, a few were found to be acting covertly, whereas the others were well known to shoppers. If retailers know and properly manage these in-store factors, they could favorably influence impulse buying, leading to an improved footfall-billing ratio. A huge proportion of retail purchasing is known to be impulse driven. If retailers understand the antecedents of impulse buying, they could harness it to their benefit. Drivers of retail impulse buying are known to be multidimensional. Social, cultural, personal, situational - all contribute their bit in influencing impulse buying. This research focuses on store characteristics that are tools in the hands of retailers for influencing impulse buying.